2018
DOI: 10.1007/s13765-018-0389-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DNA extraction methods on the detection of porcine ingredients in halal cosmetics using real-time PCR

Abstract: In recent years, halal cosmetics have attracted considerable attention worldwide. We developed a realtime PCR assay based on the mitochondrial gene ndh5 for rapid detection of porcine ingredients in halal cosmetic products. We also compared several DNA extraction methods for the most efficient approach in different types of cosmetics. Porcine template DNA was spiked into three types of cosmetics (liquid-type and powder-type mask packs, and cream) and extracted with five commercial DNA extraction kits and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
8
0
4
Order By: Relevance
“…Studies (Aviani et al, 2017;Munir et al, 2021;Widayat et al, 2019;Zabidi et al, 2020), resulted in DNA purity values. While in the study (Ishak & Mutalib, 2018;Kim et al, 2018;S Abd-Gani et al, 2019), there was no DNA purity value. The reason for measuring DNA purity with a NanoDrop Spectrophotometer is because this test is quantitative in nature, it is carried out with a NanoDrop Spectrophotometer with an absorbance ratio of 260/280 to produce an accuracy value and to validate a DNA extraction that has been carried out successfully isolated in addition to seeing the levels of DNA which are then carried out on the PCR ( Polymerase Chain Reaction ) stage, and the reason for not measuring DNA purity with the NanoDrop Spectrophotometer because this test is qualitative by looking at the parameters of the presence or absence of DNA.…”
Section: Journal Review Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies (Aviani et al, 2017;Munir et al, 2021;Widayat et al, 2019;Zabidi et al, 2020), resulted in DNA purity values. While in the study (Ishak & Mutalib, 2018;Kim et al, 2018;S Abd-Gani et al, 2019), there was no DNA purity value. The reason for measuring DNA purity with a NanoDrop Spectrophotometer is because this test is quantitative in nature, it is carried out with a NanoDrop Spectrophotometer with an absorbance ratio of 260/280 to produce an accuracy value and to validate a DNA extraction that has been carried out successfully isolated in addition to seeing the levels of DNA which are then carried out on the PCR ( Polymerase Chain Reaction ) stage, and the reason for not measuring DNA purity with the NanoDrop Spectrophotometer because this test is qualitative by looking at the parameters of the presence or absence of DNA.…”
Section: Journal Review Resultsmentioning
confidence: 76%
“…This is because at the time of testing with the Real-time PCR method there was no electrophoresis process. Real-time PCR detection limits for Power Prep TM DNA extraction kits are 100-1000 times higher than other extraction methods (Kim et al, 2018) and for Conventional PCR detection limits with lower presentations resulting in DNA amplification of 0.01% achieved for pig DNA. Each dilution series can provide good amplification up to 0.001 ng/μL but the band intensity decreases at 0.0001ng/μL dilution (Kim et al, 2018).…”
Section: Journal Review Resultsmentioning
confidence: 93%
“…Chain Reaction (PCR) [9]. Teknik tersebut dianggap valid karena karena dapat digunakan untuk mengidentifikasi spesies termasuk turunan babi secara molekuler dari level asam deoksiribonukleat (DNA) [10].…”
Section: Article Historyunclassified
“…It has been reported that isolation of DNA from rice and corn by using Wizard Genomic DNA Purification System kit from Promega is more efficient, high DNA yield and purity when compared with CTAB method (Hanum et al, 2018). However, the most suitable extraction kit for the isolation of porcine DNA from cosmetics is Power PrepTM DNA when compared with CTAB method, Nucleo spin food kit, QIAamp DNA stool mini kit, TIANamp Genomic DNA kit, and Wizard Genomic DNA purification kit (Kim et al, 2018). DNA detection method real time-PCR with DNA concentration 2.28× 10 0 copies and Ct values 39.07 was generated on porcine DNA isolated from cosmetic creams by using Power PrepTM DNA extraction kit.…”
Section: Optimization Of Dna Extraction Using Wizard Genomic Dna Purimentioning
confidence: 99%
“…It was claimed that Power PrepTM DNA extraction kit was more efficient than other extraction kits because the kit uses chloroform during the extraction process. It indicates that chloroform or hexane was used to treat oil and waxes simultaneously in lipid-rich cosmetics such as cream to reduce PCR inhibition (Kim et al, 2018).…”
Section: Optimization Of Dna Extraction Using Wizard Genomic Dna Purimentioning
confidence: 99%